Gambaran Eritrosis Kerbau Karapan yang Diberi Latihan dengan Interval Berbeda (ERYTHROCYTE PROFILES OF EXCERCISING SWAMP BUFFALOES UNDER VARIOUS EXERCISE INTERVAL) - Nyoman Sadra Dharmawan; I Gede Mahardika (Jurnal Veteriner, 2000)
Gambaran Eritrosis Kerbau Karapan yang Diberi Latihan dengan Interval Berbeda(ERYTHROCYTE PROFILES OF EXCERCISING SWAMP BUFFALOES UNDER VARIOUS EXERCISE INTERVAL)